Dapatkah Kepemilikan Tekonsentrasi Memoderasi Hubungan Tax Avoidance & Manajemen Laba Riil Dengan Nilai Perusahaan? - Melyawati, Melyawati; Trisnawati, Estralita (E-Jurnal Akuntansi; Vol 32 No 6 (2022), 2022)
The value of the company is reflected by the company's stock price which is influenced by many factors. This study examines the effect of tax avoidance and real earnings management on firm value, and examines the role of concentrated ownership as a moderating variable. The research sample is energy sector companies listed on the Indonesia Stock Exchange during 2019 and 2020. The sample was selected based on purposive sampling, the number of samples used in this study were 54 companies. The analysis technique used is Moderated Regression Analysis (MRA). Research shows that tax avoidance and real earnings management have no effect on firm value. Concentrated ownership is also unable to moderate the relationship between tax avoidance and real earnings management on firm value. Both before and during the covid-19 pandemic, did not affect the effect of these variables on the value of the company. Keywords: Firm Value; Tax Avoidance; Real Earnings Management; Ownership Concentration; Covid-19.